+0  
 
0
87
1
avatar

I = (V/R)(1-e^t)

Guest Jun 25, 2018
 #1
avatar+91297 
+2

I = (V/R)(1-e^t)     multiply both sides by  R / V

 

l (R/V)  = 1  - e^t      add e^t   to both sides and subtract  l ( R/V)  from both sides

 

e^t  =  1  - l (R / V)     take the natural log of both sides

 

Ln  e^t  = Ln ( 1  - l (R / V) )      and by a log property, we can write

 

t * Ln e   = Ln  ( 1  - l (R/V) )      and  Ln e  = 1...so we have

 

t  = Ln ( 1  - l (R/V) )

 

 

 

cool cool cool

CPhill  Jun 25, 2018

6 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.